2002
DOI: 10.1002/humu.10089
|View full text |Cite
|
Sign up to set email alerts
|

High homocysteine and thrombosis without connective tissue disorders are associated with a novel class of cystathionine β-synthase (CBS) mutations

Abstract: Cystathionine beta-synthase (CBS) is a crucial regulator of plasma levels of the thrombogenic amino acid homocysteine (Hcy). Homocystinuria due to CBS deficiency confers a dramatically increased risk of thrombosis. Early diagnosis usually occurs after the observation of ectopia lentis, mental retardation, or characteristic skeletal abnormalities. Homocystinurics with this phenotype typically carry mutations in the catalytic region of the protein that abolish CBS activity. We describe a novel class of missense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
69
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 41 publications
(48 reference statements)
12
69
2
Order By: Relevance
“…This hypothesis is based on the association of connective tissue alterations with a group of missense mutations located in the CBS C-terminal region and affecting the domain interacting with S-adenosylmethionine (AdoMet), so an increase of AdoMet cannot further stimulate CBS production. Our 2 patients with a mutation in CBS regulatory domain, carried mild cardiovascular, skeletal and cutaneous stigmas, confirming the MacLean's hypothesis [15]. Overall, the presence of a mild connective tissue involvement, including heart valve alterations and striae distensae in all 5 patients, suggests that the connective tissue pathology in homocystinuria is relevant in relation to the cardiovascular manifestations which may become more severe with aging.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…This hypothesis is based on the association of connective tissue alterations with a group of missense mutations located in the CBS C-terminal region and affecting the domain interacting with S-adenosylmethionine (AdoMet), so an increase of AdoMet cannot further stimulate CBS production. Our 2 patients with a mutation in CBS regulatory domain, carried mild cardiovascular, skeletal and cutaneous stigmas, confirming the MacLean's hypothesis [15]. Overall, the presence of a mild connective tissue involvement, including heart valve alterations and striae distensae in all 5 patients, suggests that the connective tissue pathology in homocystinuria is relevant in relation to the cardiovascular manifestations which may become more severe with aging.…”
supporting
confidence: 84%
“…MacLean et al [15] suggested that clinical homocystinuric manifestations related to the connective tissue may be correlated to the decrease of CBS production causing both an increase of hcy levels and a decrease of cysteines. The decrease of cysteines may affect the qualitative and quantitative synthesis of connective tissue proteins causing EL and other connective tissue manifestations.…”
mentioning
confidence: 99%
“…Women with CBS deficiency are at increased risk for thrombosis during pregnancy and the literature documents CBS patients diagnosed, as was our patient, in the peripartum period (Kurczynski et al 1980;Constantine and Green 1987;Yap et al 2001;Levy et al 2002;Pierre et al 2006). Patients without severe connective tissue complications may present in adulthood (Maclean et al 2002;Magner et al 2011). In addition some patients are confused with Marfan Syndrome as was patient 1 (Berry and Levy 2010).…”
Section: Discussionsupporting
confidence: 57%
“…Mutations at the C-terminal region are rare among homocystinuric patients. Recently, three C-terminal mutations have been described and their activity has been assayed by expressing them in E.coli [Maclean et al, 2002]. It was found that they were all 100% or more active but were unable to respond to AdoMet.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%